Another step closer to measuring the ghosts in the nursery: preliminary validation of the Trauma Reflective Functioning Scale - Ensink, Karin; Berthelot, Nicolas; Bernazzani, Odette; Normandin, Lina; Fonagy, Peter (Frontiers in Psychology, 2014)
The aim of this study was to examine preliminary evidence of the validity of the Trauma Reflective Functioning Scale and to investigate reflective functioning and attachment in pregnant women with histories of trauma, with a particular focus on the capacity to mentalize regarding trauma and its implications for adaptation to pregnancy and couple functioning. The Adult Attachment Interview was used to assess attachment, unresolved trauma and mentalization (measured as reflective function; RF) regarding relationships with attachment figures (RF-G) and trauma (RF-T) in 100 pregnant women with histories of abuse and neglect. The majority (63%) of women had insecure attachment states of mind and approximately half were unresolved regarding trauma. Furthermore, the majority of women manifested deficits specific to RF-T. Their RF-T was significantly lower than their RF-G; the findings indicate that women with histories of childhood abuse and neglect do not manifest a generic inhibition of reflectiveness, but a collapse of mentalization specific to trauma. Low RF-T, indicative of difficulty in considering traumatic experiences in mental state terms, was associated with difficulty in investment in the pregnancy and lack of positive feelings about the baby and motherhood. In addition, low RF-T was also associated with difficulties in intimate relationships. Results of a regression analysis with RF indicated that RF-T was the best predictor of investment in pregnancy and couple functioning. In sum, the study provides preliminary evidence that RF-T can be reliably measured and is a valid construct that has potential usefulness for research and clinical practice. It highlights the importance of mentalization specifically about trauma and suggests that it is not the experience of trauma per se, but the absence of mentalization regarding trauma that is associated with difficulties in close relationships and in making the transition to parenthood.